2016
DOI: 10.1177/1043659616661612
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Pap Screening Use Among African Immigrant Women

Abstract: Interventions addressing the barriers peculiar to this population may alleviate these barriers and improve Pap screening use in this population. Providers have the opportunity to influence screening attitudes of African-born women by providing awareness and patient-targeted interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 41 publications
(69 reference statements)
6
24
0
Order By: Relevance
“…The most commonly mentioned barriers were related to language difficulties and misunderstanding of the invitation letters’ contents, again consistent with previous findings [ 33 , 40 , 45 , 52 , 54 , 63 ]. In Finland, at the time of this study, the invitation letter is written in both official Finnish languages (Finnish/Swedish); this explains the women’s difficulties in reading and understanding the screening information.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most commonly mentioned barriers were related to language difficulties and misunderstanding of the invitation letters’ contents, again consistent with previous findings [ 33 , 40 , 45 , 52 , 54 , 63 ]. In Finland, at the time of this study, the invitation letter is written in both official Finnish languages (Finnish/Swedish); this explains the women’s difficulties in reading and understanding the screening information.…”
Section: Discussionsupporting
confidence: 90%
“…Several individual-related barriers to CCS participation have been identified, e.g., unmarried, unemployed, illiteracy/lower education level, and language difficulties [ 27 , 31 , 33 , 35 , 37 , 40 ]; women’s lack of knowledge/awareness of cancer/risk factors or screening practices, unpleasant experiences of screening such as pain, embarrassment, and obesity [ 34 , 41 , 42 , 43 , 44 , 45 , 46 ]; and advanced age and no history of pregnancy or birth [ 27 , 30 , 33 , 47 , 48 ]. Other factors have been considered, such as migration-related issues in the host country [ 31 , 33 , 35 , 49 ], women’s fear of cancer or test results, and cultural and religious beliefs [ 43 , 45 , 50 , 51 , 52 , 53 , 54 ]. System-related barriers include mistrust of healthcare authorities, inaccessibility to healthcare or/and interpretation services, and concern about the gender of the test-taker [ 40 , 45 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Authors (year of publication) Study type/design Sample/size Group/study focus Adegboyega and Hatcher (2016) Qualitative study/focus group 22 [Sub-Sahara] African immigrants Adegboyega and Hawkins (2016) Literature review [Sub-Sahara] African immigrants Brown, Ham-Baloyi, van Rooyen, Aldous, and Marais 2016Quantitative/survey 468 African Americans and African immigrants Lang et al (2013) Quantitative/survey 733 African Americans S. Lee, O'Neill, Ihara, and Chae (2013) Quantitative/secondary data analysis 5,982 Different groups of immigrants Mays, Cochran, and Barnes (2007) Literature review African Americans Murray, Mohamed, and Ndunduyenge Another study (Mays et al, 2007) distinguished cause and effect relationships linking racial-ethnic and health disadvantage that further contributes to the harmful effects of the chronic experiences of race-based discrimination. These chronic experiences are thought to set into motion the physiological responses of elevated heart rate, blood pressure, increased production of biochemical reactions, and hypervigilance that eventually lead to earlier onset of disease and mortality (Mays et al, 2007).…”
Section: Nomentioning
confidence: 99%
“…African immigrants are subject to a "double-jeopardy," where they are grouped with African Americans based on race (Pavlish et al, 2010). During hospitalization, African immigrants have reported being treated differently based on their accents and cultural mode of dressing (Adegboyega & Hatcher, 2016;Adegboyega & Hawkins, 2016). Based on Boise et al (2013) study, African immigrants have reported receiving poor and insensitive care as well as disrespect from health care providers who they believe portray racist attitudes and do not treat them as "whole" people but rather as poor, minority newcomers at the bottom of the sociocultural ladder.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation